POPULASI BANGAU STORM (Ciconia stormi W. Blasius) DI KAWASAN HUTAN SUNGAI KEPULUK KECAMATAN MATAN HILIR SELATAN KABUPATEN KETAPANG KALIMANTAN BARAT - Purbowo, Satriyo DS; Nurdjali, Bachrun; Dewantara, Iswan (Universitas Tanjungpura, 2017)
Storm's Stork (Ciconia stormi W. Blasius in the category International Union for Conservation of Nature and Natural Resources (IUCN) Red List of Endangered. This research is could provide preliminary information on the number of individuals Stork Storm which is expected to be considered in efforts to conserve wild bird species in the future in The Kepuluk River Matan Hilir Selatan District Ketapang Regency West Kalimantan. The method used in this research is the lines transect with a width of 50 meters to the left lane and 50 meters to the right and a length of 1 km transect, based on the result of the observation on the average fathoming score population in Bangau Storm in research location is about 23,5990 Bangau with on the average solid 0,7866 Bangau per hectare. Based on the observation have been done, this research get representation that Kepuluk river is one of mullet can use for Bangau Storm existence, although there are some disturbances in research location which is can threaten this wild animal such as forest fire, the hunt activity, the activity of mining gold illegal and felling of trees illegal. Keywords: Population of Storm’s stork, Kepuluk River.